IMF Staff papers : Volume 27 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1980)
This paper analyzes the types of fiscal performance clauses incorporated in the 105 arrangements, bearing in mind the policy and practice to avoid performance clauses relating to specific fiscal measures, such as changes in particular forms of taxation and changes in specific elements of government expenditure. The most usual fiscal performance clause in the ten years to 1978 continued to be a sub ceiling on domestic bank credit to the government. A ceiling on credit expansion to this sector has proved to be a helpful technique for national authorities in obtaining political support for adequate fiscal policy actions and in retaining such support over time. A number of cases were noted where arrears in government payments were built up during the program period, sometimes in an effort to observe, technically, the relevant credit ceilings. It could be argued that such a practice, while not in the spirit of the agreement, forces a diversion of financial resources away from the private sector to the government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet